2010
DOI: 10.1029/2009jb006567
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes of subsurface velocities during strong shaking as seen from seismic interferometry

Abstract: [1] We apply a deconvolution method to a strong motion data set recorded at the surface and in boreholes in northeast Honshu, Japan. We try to characterize the nonlinear effects of the subsurface soil during strong shaking and show the change of the subsurface velocity structure during the shaking. The deconvolved waveforms reflect the subsurface velocity structure, and their horizontal and vertical components correspond to S and P wave, respectively, traveling from the borehole to the ground surface. The stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…D(w) is the frequencydomain waveform that propagates from the borehole sensor to the surface sensor [Snieder and Şafak, 2006;Mehta et al, 2007;Sawazaki et al, 2009;Yamada et al, 2010]. We choose to be 1% of the average power spectrum of the wavefield at the borehole receiver because we find experimentally this is the smallest value of the regularization parameter that produces stable deconvolved wavefields.…”
Section: Deconvolution Interferometrymentioning
confidence: 99%
“…D(w) is the frequencydomain waveform that propagates from the borehole sensor to the surface sensor [Snieder and Şafak, 2006;Mehta et al, 2007;Sawazaki et al, 2009;Yamada et al, 2010]. We choose to be 1% of the average power spectrum of the wavefield at the borehole receiver because we find experimentally this is the smallest value of the regularization parameter that produces stable deconvolved wavefields.…”
Section: Deconvolution Interferometrymentioning
confidence: 99%
“…Previous studies extracted time lapse changes caused by earthquakes [Li et al, 1998;Vidale and Li, 2003;Schaff and Beroza, 2004;Wegler and Sens-Schönfelder, 2007;Brenguier et al, 2008]. Interferometry applied to a single KiK-net station has also been used to measure time lapse change due to earthquakes [Sawazaki et al, 2009;Yamada et al, 2010]. Interferometric studies have shown changes in the shear wave velocity caused by precipitation [Sens-Schönfelder and Wegler, 2006] and have measured shear wave splitting [Bakulin and Mateeva, 2008;Miyazawa et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…By using these networks for seismic interferometry, Tonegawa et al [2009] extract the deep subsurface structure of the Philippine Sea slab. These data have also been used to observe time lapse changes in small regions [Wegler and Sens-Schönfelder, 2007;Sawazaki et al, 2009;Wegler et al, 2009;Yamada et al, 2010]. Each KiK-net station has two receivers, one on the ground surface and the other at the bottom of a borehole.…”
Section: Introductionmentioning
confidence: 99%
“…At present, field observations in geophysics have shown that acoustoleastic constant (relative-wave-velocity sensitivity to the initial stresses) of the FSPR is much greater than that of metal materials (Cheng et al, 2010;Nakata and Snieder, 2011;Niu et al, 2008;Sayers, 2010;Tosaya, 1982;Yamada et al, 2010). In addition, acoustoelastic effect of the FSPR has also been verified in rock experiments (Sayers, 2010).…”
Section: Introductionmentioning
confidence: 87%